2021
DOI: 10.1101/2021.03.26.437137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A projectome of the bumblebee central complex

Abstract: Insects have evolved diverse and remarkable strategies for navigating in various ecologies all over the world. Regardless of species, insects share the presence of a group of morphologically conserved neuropils known collectively as the central complex (CX). The CX is a navigational hub, involved in sensory integration and coordinated motor activity. Despite the fact that our understanding of navigational behavior comes predominantly from ants and bees, most of what we know about the underlying neural circuitr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Work in Drosophila shows that subsets of these neurons play an important role in transforming the heading signal from body‐centric to world‐centric coordinates (Lu et al., 2022; Lyu et al., 2022). In bumblebees, it was shown that PFN neurons are the most abundant columnar cell type in the CX with a total count of 854 (Sayre et al., 2021). As in CL neurons, where isomorphic sets of neurons can be distinguished by their peptide‐ or transmitter content, the AST antiserum labels only a subset of these neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Work in Drosophila shows that subsets of these neurons play an important role in transforming the heading signal from body‐centric to world‐centric coordinates (Lu et al., 2022; Lyu et al., 2022). In bumblebees, it was shown that PFN neurons are the most abundant columnar cell type in the CX with a total count of 854 (Sayre et al., 2021). As in CL neurons, where isomorphic sets of neurons can be distinguished by their peptide‐ or transmitter content, the AST antiserum labels only a subset of these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study from our group provides an anatomical description of neuronal cell types in the CX of honeybees (Hensgen et al., 2020). Many of these neurons have also been found in the highly similar CX of bumblebees (Sayre et al., 2021). Here, we extend this base by providing a three‐dimensional atlas of the honeybee's CX and associated neuropils, which includes distinct layers of the central body derived from neuropeptidergic immunostaining.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent gains in understanding the neural circuitry that likely underlies path integration in bees has yielded a region of the arthropod brain termed the central complex as the main cellular substrate for path integration and general navigation control. This progress is based on comparisons between detailed electron-microscopical maps of the central complexes of flies 33 and bumblebees 34 , combined with physiological data and anatomically constrained computational models in a sweat bee 35 . However, to link neural circuits of the central complex to the sophisticated path integration abilities of hymenopteran insects, circuit data need to be combined with functional and behavioral data in a single model species.…”
Section: Introductionmentioning
confidence: 99%